Endangered and Threatened Fishes in the Klamath River Basin: Causes of Decline and Strategies for Recovery - National Research Council (The National Academies Press, 2004)
In 1988 the U.S. Fish and Wildlife Service listed two endemic fishes of the upper Klamath River basin of Oregon and California, the sucker and the Lost River sucker, as endangered under the federal Endangered Species Act (ESA). In 1997, the National Marine Fisheries Service added the Southern Oregon Northern coastal California (SONCC) coho salmon as a threatened species to the list. The leading factors attributed to the decline of these species were overfishing, blockage of migration, entrainment by water management structures, habitat degradation, nonnative species, and poor water quality. Endangered and Threatened Fishes of the Klamath River Basin addresses the scientific aspects related to the continued survival of coho salmon and shortnose and Lost River suckers in the Klamath River. The book further examines and identifies gaps in the knowledge and scientific information needed for recovery of the listed species and proves an assessment of scientific considerations relevant to strategies for promoting the recovery of those species.
Keywords: Environment and Environmental Studies; Agriculture; Biology and Life Sciences

Review of the U.S. Army Corps of Engineers Restructured Upper Mississippi River-Illinois Waterway Feasibility Study: Second Report - Transportation Research Board; National Research Council (The National Academies Press, 2004)
For the past few years, the Corps has been working on what is known as the Restructured Upper Mississippi River-Illinois Waterway Feasibility Study, the heart of which is a multibillion-dollar proposal to double the length of up to a dozen locks on the river. The Research Council first reviewed the feasibility study in 2001 during controversies over the accuracy of models being used by the Corps to justify lock expansion based on increased demand for barge transportation. More than 100 million tons of cargo--half of it grain destined for international markets, the other half goods such as construction materials, coal, and chemicals--are shipped along the navigation system each year. The locks, which along with dams allow barges to traverse uneven river depths, were originally designed for "tows" of barges up to 600 feet long, but the length of a typical tow has increased, forcing the Corps to look for ways to relieve congestion. The book finds the U.S. Army Corps of Engineers has made good progress in broadening its proposed plan for navigation improvements on the Upper Mississippi River-Illinois Waterway system to give greater consideration to ecological restoration. However, the plan still does not provide sufficient economic justification for expanding locks on the rivers because of flaws in the models the Corps used to predict demand for barge transportation. Little attention is paid to inexpensive, nonstructural navigation improvements that could help better manage existing levels of barge traffic. The revised plan has been usefully expanded to include many creative and potentially useful ecosystem restoration measures. These measures, however, should be more firmly grounded in river science principles and more broadly consider ways the river's ecology might affect or be affected by navigation, recreation and other uses.
Keywords: Earth Sciences

Atlantic Salmon in Maine - National Research Council (The National Academies Press, 2004)
Because of the pervasive and substantial decline of Atlantic salmon populations in Maine over the past 150 years, and because they are close to extinction, a comprehensive statewide action should be taken now to ensure their survival. The populations of Atlantic salmon have declined drastically, from an estimated half million adult salmon returning to U.S. rivers each year in the early 1800s to perhaps as few as 1,000 in 2001. The report recommends implementing a formalized decision-making approach to establish priorities, evaluate options and coordinate plans for conserving and restoring the salmon.
Keywords: Agriculture; Environment and Environmental Studies; Biology and Life Sciences

Adaptive Management for Water Resources Project Planning - National Research Council (The National Academies Press, 2004)
This book reviews the Corps of Engineers' experiences to date with the concept of “adaptive management” and provides advice on additional and more effective implementation of this planning approach. The adaptive management concept itself is complex and evolving, but might be summarized as “learning while doing.” The book reviews literature on adaptive management and notes that a range of adaptive management practices present themselves for Corps projects. It is noted that there is no “cookbook” approach to adaptive management, and the book encourages the Corps of Engineers to continue to work with and learn from its applications of the concept. To facilitate institutional learning and to ensure that experiences are being employed across the agency, the book recommends that a Corps Center for Adaptive Management be established. The book also notes that greater involvement from the administration and Congress will be essential to successful adaptive management applications, as the Corps' efforts in this area will benefit from clarified water resources management objectives, the authority to manage adaptively, and from resources necessary for programs such as stakeholder collaboration and post-construction evaluations.
Keywords: Earth Sciences

Managing the Columbia River: Instream Flows, Water Withdrawals, and Salmon Survival - National Research Council (The National Academies Press, 2004)
Flows of the Columbia River, although modified substantially during the twentieth century, still vary considerably between seasons and between years. Lowest flows tend to occur during summer months when demand for irrigation water is at its highest and when water temperatures are greatest. These periods of low flows, high demand, and high temperature are critical periods for juvenile salmon migrating downstream through the Columbia River hydropower system. Although impacts on salmon of any individual water withdrawal may be small, the cumulative effects of numerous withdrawals will affect Columbia River flows and would pose increased risks to salmon survival. The body of scientific knowledge explaining salmon migratory behavior and physiology is substantial, but imperfect, and decision makers should acknowledge this and be willing to take action in the face of uncertainties. In order to provide a more comprehensive water permitting process, the State of Washington, Canada, other basin states, and tribal groups should establish a basin-wide forum to consider future water withdrawal application permits. If the State of Washington issues additional permits for water withdrawals from the Columbia River, those permits should contain provisions that allow withdrawals to be curtailed during critical high-demand periods.
Keywords: Agriculture; Earth Sciences

Review of the U.S. Army Corps of Engineers Restructured Upper Mississippi-Illinois River Waterway Feasibility Study - Transportation Research Board; National Research Council (The National Academies Press, 2004)
The U.S. Army Corps of Engineers has a long history of managing navigation, floods, and other water-related issues on the Upper Mississippi and Illinois Rivers. A recent chapter in that history is the problem of waterway congestion at several locks on the lower portion of the Upper Mississippi River. The Corps has studied this problem and its possible solutions since the late 1980s, producing a draft feasibility study in 2000 and an interim report on a restructured feasibility study in 2002. A committee was convened to review and provide advice on the most recent phase of the Corps' analytical efforts.
Keywords: Earth Sciences

U.S. Army Corps of Engineers Water Resources Planning: A New Opportunity for Service - National Research Council (The National Academies Press, 2004)
From the Executive Summary: There are some concerns that the current Corps planning and construction budget has not kept pace with expanding national water management needs for flood hazard management, water transportation, and other purposes. At the same time, others question the wisdom of and budgetary prospects for the continuation of a traditional water project construction program. Debates about water use and funding priorities now extend to intense scrutiny of Corps of Engineers planning, investment, and project operations programs.
Keywords: Earth Sciences

River Basins and Coastal Systems Planning Within the U.S. Army Corps of Engineers - National Research Council (The National Academies Press, 2004)
The U.S. Army Corps of Engineers (the Corps) has played a large and important role in shaping water resources systems in the United States since Congress first tasked it in 1824 to improve navigation on the Ohio and Mississippi Rivers. Since then, rivers have been modified for navigation and flood control, harbors have been dredged for shipping, and coastlines are routinely fortified against erosion and beach loss. Recent decades have seen an overall decline in budgets for civil works project construction, yet the range of objectives for water resources projects has broadened as society places more value on environmental and recreational benefits. Thus, the Corps' portfolio of water resources projects has changed considerably. There is a reduced emphasis on traditional construction projects and an increased focus on maintenance and reoperation of existing projects such as locks, dams, and levees and on environmental restoration projects. An integrated approach to water resources planning at the scale of river basins and coastal systems is widely endorsed by the academic and engineering communities. The Corps' mission, expertise, and experience give it immense potential to alter the structure and functioning of the nation's waterways and coasts. As might be expected in a large and complex organization answering to a range of public and private demands, implementation of these new policies and objectives is neither consistent nor complete. River Basins and Coastal Systems Planning within the U.S. Army Corps of Engineers recommends improvements in the Corps' water resource project planning and review process. This report compares economic and environmental benefits and costs over a range of time and space scales, suggests multiple purpose formulation and evaluation methods, and recommends integration of water development plans with other projects in the region.
Keywords: Earth Sciences

Analytical Methods and Approaches for Water Resources Project Planning - National Research Council (The National Academies Press, 2004)
Analytical Methods and Approaches for Water Resources Project Planningis part of a larger study that was conducted in response to a request from the U.S. Congress in the Water Resources Development Act of 2000 for the National Academy of Sciences to review the U.S. Army Corps of Engineer's peer review methods and analytical approaches. This report reviews the Corps' analytical procedures and planning methods, largely in the context of the federal Economic and Environmental Principles and Guidelines for Water and Related Land Resources Implementation Studies, also known as the Principles and Guidelines or "P and G" (P&G), as well as the Corps' Planning Guidance Notebook (PGN).
Keywords: Earth Sciences